2021
DOI: 10.33590/emjdermatol/20-00202
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxins in Medical and Cosmetic Dermatology

Abstract: Background: Botulinum toxin (BoNT), a bacterially produced neurotoxin, is a mainstay in the dermatologic armamentarium. Although BoNT is commonly used to treated rhytides associated with ageing, it can be employed for a variety of other cosmetic purposes and medical disorders. Objective: In this review, the authors aim to describe the multitude of uses for BoNT in the dermatologic field. Materials and Methods: This manuscript was designed as a retrospective review of the on- and off-label applications of BoNT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…As higher PFM strength is associated with better sexual function and particularly with a greater facility to achieve climax [32], this adverse event could be explained by BoNT/A's chemical denervation of motor units in the muscle, which thus became unable to contract and develop strength. As both adverse events were mild and transient, this study adds to previous findings that confirmed BoNT/A injected in limited doses can be safely used to treat vestibulodynia [33].…”
Section: Patients' Evolution After Treatment: Adverse Eventssupporting
confidence: 67%
“…As higher PFM strength is associated with better sexual function and particularly with a greater facility to achieve climax [32], this adverse event could be explained by BoNT/A's chemical denervation of motor units in the muscle, which thus became unable to contract and develop strength. As both adverse events were mild and transient, this study adds to previous findings that confirmed BoNT/A injected in limited doses can be safely used to treat vestibulodynia [33].…”
Section: Patients' Evolution After Treatment: Adverse Eventssupporting
confidence: 67%
“…The FDA (Food and Drug Administration, USA) has approved for use four types of neuroprotein type A: onabotulinumtoxinA, abobotulinumtoxinA, incobotu-linumtoxinA, prabotulinumtoxinA-xvfs and one type B -rimabotulinumtoxinB [34]. However, botulinum toxin type A is used in cosmetology practice the average duration of the effect of injection of which is 12 weeks [32,35].…”
Section: сучасні підходи до корекції вікових змін шкіри у жінок г і м...mentioning
confidence: 99%
“…2 In the United States, there are four commercially available, FDA-approved BoNT-A formulations: incobotulinumtoxinA (Frankfurt, Germany), onabotulinumtoxinA (California, USA), prabotulinumtoxinA-xvfs (California, USA) and abobotulinumtoxinA (Arizona, USA); as well as one BoNT-B: rimabotulinumtoxinB (California, USA). 5 A review by Guida et al 6 evaluated the role of BoNT in the field of dermatology. However, recently there are no reviews conducted on the application of BoNT in the field of dermatology and cosmetology.…”
Section: Introductionmentioning
confidence: 99%